(untitled) (Hoboken, N.J., 2012)
SQL Server 2012 is packed with powerful new Analysis Services features that will dramatically enhance business intelligence. Written by key members to Microsoft's product team, this book shows you how to apply these new capabilities to create sophisticated BI solutions. In order to accomplish this, you'll learn how to design, build, and work with the multidimensional and tabular Business Intelligence Semantic Model (BISM) using SQL Server Analysis Services. You'll then use MDX and DAX to query those databases so you can provide advanced analysis of business problems and build end-to-end solutions to meet your needs
Keywords: Database management,Quản lý cơ sở dữ liệu